Hubungan Sikap Ibu Dengan Status Gizi Pada Balita Di Desa Kemuning Lor, Arjasa, Jember - Eka Afdi Septiyono; Lantin Sulistyorini; Faridha Nur Qomariah; Intan Dwi Arini (Jurnal Kesehatan dr. Soebandi, 2019)
Nutrition is the organic substance needed by the body. Nutrition is one of the important factors influencing the growth and development of humans. But right now, undernutrition in Indonesia is being a central problem. Undernutrition is a condition where someone’s nutritional state is lower than standard which is <-3SD weight/age. One of the factors that caused undernutrition in a toddler is the mother’s attitude. The purpose of this study was to analyze the correlation between mother’s attitude and nutritional status in toddlers in Kemuning Lor Village, Arjasa District, Jember Regency. The type of this research was descriptive-analytic using a cross-sectional approach. The sample of this research is 156 respondents taken using a purposive sampling technique. Data analyzed with Chi-Square Test. The result of this research showed that most of the mother’s attitude was (53,6%) sufficiently and most of the nutritional status in a toddler was (80,8%) normal. The data analytical by Chi-Square Test (CI = 95%) and result showed p-value 0,003 (p-value > α = 0,05). In conclusion, there was a correlation mother’s attitude and nutritional status in toddlers in Kemuning Lor Village, Arjasa District, Jember Regency. A good mother’s attitude can impact the mother’s effort in increasing the intake of nutrition so that it can improve the nutritional status of the toddler.sta